Analisis Pengaruh Perputaran Kas, Perputaran Piutang dan Perputaran Total Aset terhadap Profitabilitas pada Koperasi Jasa Karyawan Angkasa - Ni Made Mega Sriwahyuni; Ni Wayan Ari Sudiartini; Ni Ketut Murdani (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Cooperatives are membership-based economic entities that play a vital role in driving the growth of the microeconomic sector and improving member welfare through the principles of economic democracy. The sustainability of cooperative performance heavily depends on effective financial management, particularly in maximizing the utilization of cash, receivables, and assets to enhance profitability. This study aims to examine the influence of cash turnover, receivables turnover, and total asset turnover on the profitability of cooperatives, as measured by Return on Assets (ROA) as a financial performance indicator. The research employs a quantitative approach using multiple linear regression analysis, based on secondary data from cooperative financial statements covering the period from 2019 to 2024. The analysis results show that both simultaneously and partially, the three independent variables have a positive and significant effect on profitability. Cash turnover and total asset turnover are the primary determinants in improving ROA, reflecting the importance of efficiency in managing liquidity and productive assets. Meanwhile, although receivables turnover is also significant, it requires strict supervision in the implementation of credit policies to avoid an increase in non-performing receivables. These findings contribute empirical evidence to the literature on cooperative financial management and offer practical implications for cooperative managers in designing financial resource management strategies aimed at improving performance and business sustainability. Therefore, optimizing the management of cash, receivables, and assets should be a strategic priority within cooperative financial systems to withstand increasingly complex and competitive economic dynamics.